Pengaruh Ketidakpedulian Keluarga terhadap Perilaku Remaja Desa Amplas - Amalia Ramadhani Suci Ardi; Ali Darta; Nurselina Nasution; T. Wulan Arianti (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This study aims to determine how the influence of families in juvenile delinquency that is rampant at this time and also the main factors that trigger juvenile delinquency. Juvenile delinquency is a form of social neglect caused by the surrounding environment, thus developing a form of deviant behavior. The research method used is a quantitative method. The data collection technique used was through interviews with village officials and community leaders from Amplas village as well as observations to the community. The results in this study are the factors that influence juvenile delinquency in Amplas Village due to unsupportive family conditions, lack of parental supervision and care, bad or negative social situations of teenagers, so that it has an impact on teenagers to commit deviant acts, waning culture. manners and misuse of technology or social media.